The space for challenge in transnational education governance: the case of Education International and the OECD TALIS programme. Issue 4 (4th July 2021) - Sorensen, Tore Bernt
ABSTRACT: The article provides an explanatory critique of the engagement of Education International in the Teaching and Learning International Survey (TALIS), a programme coordinated by the Organisation for Economic Co-operation and Development. Drawing on research interviews, I adopt the framework advocated by Isabela and Norman Fairclough for analysing political discourse as practical argumentation, and the concept of institutional power resources. I show that the engagement of Education International in TALIS represents a strategy of getting involved in the politics of knowledge as a lever for teacher voice in transnational governance. On this basis, I discuss the space for challenge in transnational education governance, with a focus on the power capacity of Education International and the implications of enhancing institutional power resources within the context of an unfolding education policy field that is transnational in scope, thickening in its trajectory, and pluri-scalar in its nature.